'Navigating the bubble': Exploring student experiences of design writing. (1st January 2021) - Smith, Catherine
Undergraduate design students at London College of Communication were interviewed about the relationship between their writing practice and their design practice. Gardner's theory of multiple intelligences (1983) framed the study. This article takes the position that polarizing the relationship between linguistic (textual) and bodily kinaesthetic (visual) forms of intelligence itself becomes a barrier to arts students' epistemological development. The well-rehearsed art school rhetoric of 'I'm a visual person not a writer' can become a self-fulfilling prophecy, disabling the potential to learn through writing. The research explored student perceptions and experiences of design writing, with data surfacing themes of anxiety, identity, artefact, articulation, process and value. Suggestions about how to support students to write about design praxis are presented for consideration.